2014
DOI: 10.3109/09513590.2014.958991
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of involvement of angiotensin II, its receptors, and androgen receptor in endometrial cancer

Abstract: Endometrial cancer (EC) is the most common gynecological malignancy. Alterations of angiogenic factors including angiotensin (AngII) or VEGF are observed in EC. Expression of angiotensin receptor 1 (AT1) is correlated with EC. Moreover, the expression of VEGF is up-regulated by AngII. Androgens are involved in the pathogenesis of EC. Genetic variations in androgen receptor (AR) gene may increase EC risk. This review proved strong correlation among EC, AngII, its receptors and AR, where AT influence on AR and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…EC cases diagnosed with non-endometrioid type II lesions also presented with significantly higher levels of adrenal precursors and androgens but not estrogens, suggesting an influence of the tumor on the adrenal secretion and on peripheral conversion of adrenal precursors to androgens with no subsequent impact on aromatization. This is in agreement with recent studies sustaining that androgens may play an etiological role in Type II EC, independent of their conversion to estrogens [41][42][43]. Furthermore, certain risk factors such as cigarette smoking and alcohol intake might influence cancer risk by altering adrenal precursors and androgen levels [44].…”
Section: Discussionsupporting
confidence: 92%
“…EC cases diagnosed with non-endometrioid type II lesions also presented with significantly higher levels of adrenal precursors and androgens but not estrogens, suggesting an influence of the tumor on the adrenal secretion and on peripheral conversion of adrenal precursors to androgens with no subsequent impact on aromatization. This is in agreement with recent studies sustaining that androgens may play an etiological role in Type II EC, independent of their conversion to estrogens [41][42][43]. Furthermore, certain risk factors such as cigarette smoking and alcohol intake might influence cancer risk by altering adrenal precursors and androgen levels [44].…”
Section: Discussionsupporting
confidence: 92%
“…It was further concluded that T/C polymorphism may not directly be associated with the PCOS. The association may rely on the polymorphism when there is increased level of testosterone and insulin resistance [39].…”
Section: Aromatase and Pcosmentioning
confidence: 99%
“…Accumulating evidence suggests that circulating ANGPTL8 is elevated in diabetes [ 73 85 , 104 ]. Diabetes is often associated with diabetic dyslipidaemia, characterized by hypertriglyceridaemia, lower HDL-C and postprandial lipaemia [ 105 ].…”
Section: Perspectivementioning
confidence: 99%